Non-Formal Primary Education (NFPE) programme proposal for phase II, April 1996-March 1999 - BRAC (© BRAC, 2016)
1. Primary education in Bangladesh 2. BRAC'S development strategy 3. Non-Formal Primary Education: The BRAC solution 4. NFPE expansion phase I: 1992-1995 5. Non-Formal Primary Education:April 1996-March 1999 6. Budget.